Teachers' experiences with K‐12 students' mental health. Issue 5 (2nd February 2022) - Deaton, Jennifer D.; Ohrt, Jonathan H.; Linich, Kathryn; Wymer, Brooke; Toomey, Mitchell; Lewis, Olivia; Guest, Jessie D.; Newton, Therese
Abstract: The purpose of this study was to explore teachers' experiences of student mental health concerns (SMHC) in the classroom. In this consensual qualitative research (CQR) study, we explored 12 teachers' experiences related to their SMHCs in the classroom. Five domains emerged from this CQR study: (1) Teachers' Responses to Student Mental Health Concern s, (2) Teachers' Perceptions of Preparedness in Addressing Student Mental Health, (3) Teacher Identified Preparation Needs to Addressing Student Mental Health, (4) Divergent Experiences of Support for Student Mental Health, and (5) Student Mental Health Influences . Overall, teachers lack the training and support to address SMHC in the classroom, resulting in numerous attempts of trial and error. These participants emphasize the need for training in SMHCs commonly found in children and adolescents coupled with classroom strategies to support these students' needs.